Social media, sociality, and survey research - Hill, Craig A., 1956-; Dean, Elizabeth, 1974-; Murphy, Joe, 1974- (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
Provides the knowledge and tools needed for the future of survey research The survey research discipline faces unprecedented challenges, such as falling response rates, inadequate sampling frames, and antiquated approaches and tools. Addressing this changing landscape, Social Media, Sociality, and Survey Research introduces readers to a multitude of new techniques in data collection in one of the fastest developing areas of survey research. The book is organized around the central idea of a ""sociality hierarchy"" in social media interactions, comprised of three le.
Social media, sociality, and survey research / Joe Murphy, Craig A. Hill, and Elizabeth Dean -- Sentiment analysis : providing categorical insight into unstructured textual data / Carol Haney -- Can Tweets replace polls? : a U.S. health-care reform case study / Annice Kim, Joe Murphy, Ashley Richards, Heather Hansen, Rebecca Powell, and Carol Haney -- The Facebook platform and the future of social research / Adam Sage -- Virtual cognitive interviewing using Skype and Second Life / Elizabeth Dean, Brian Head, and Jodi Swicegood -- Second Life as a survey lab : exploring the randomized response technique in a virtual setting / Ashley Richards and Elizabeth Dean -- Decisions, observations, and considerations for developing a mobile survey app and panel / David Roe, Yuying Zhang, and Michael Keating -- Crowdsourcing : a flexible method for innovation, data collection, and analysis in social science research / Michael Keating, Bryan Rhodes, and Ashley Richards -- Collecting diary data on Twitter / Ashley Richards, Elizabeth Dean, and Sarah Cook -- Recruiting participants with chronic conditions in Second Life / Saira N. Haque and Jodi Swicegood -- Gamification of market research / Jon Puleston -- The future of social media, sociality, and survey research / Craig A. Hill and Jill Dever -- Index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Online social networks -- Research; Social media -- Research; Social surveys -- Methodology; PSYCHOLOGY / Social Psychology; Online social networks -- Research; Social media -- Research; Social surveys -- Methodology; Electronic books; Electronic books